Implementation of the Simple Additive Weighting Method as a Decision Support in the Selection of the Right Drug Supplier - Natasha Zulkarnain; Helma (Rangkiang Mathematics Journal, 2023)
Supplier is a business relationship that plays a crucial role in securing the logistics of medicines needed by pharmacies. The large number of suppliers makes it difficult to determine a good supplier. For this reason, an overview of supplier selection is needed according to the criteria expected by the pharmacy using the Simple Additive Weighting method. This study aims to find out the best drug suppliers for the types of drugs Paracetamol 500 mg tablets and Ambroxol 30 mg tablets. The data processed is in the form of data on quality, delivery, price, trust, and responsiveness. In the Simple Additive Weighting (SAW) method, the assessment of each criterion is obtained from the assessment of the assistant pharmacist at the Ridho Farma Pharmacy itself, then proceed with the matrix normalization process based on the equation adjusted for the type of criteria (benefit criteria or cost criteria) so that a normalized matrix is ​​obtained. and proceed with the ranking process. The research results obtained are priority suppliers of Paracetamol 500 mg tablets, namely PT. Penta Valent and the priority supplier for Ambroxol 30 mg tablets are PT. Tri Sapta Jaya.